Host–parasite relationships and life cycles of cuckoo wasps in agro-ecosystems in Argentina (Hymenoptera: Chrysididae: Chrysidini) - Torretta, Juan Pablo (2015)
Chrysididae is a diverse group of parasitoid/cleptoparasitic wasps; however, host– parasite relationships and life cycles of few species have been studied. Nests of different wasp and bee species were obtained during a trap-nesting programme, in the Pampean region. Some of these nests were parasitised by cuckoo wasps females of Caenochrysis taschenbergi (Mocsáry), Chrysis boutheryi (Brèthes), C. saltana Bohart, C. sp. 1 (ignita-group), C. sp. 2 (ignita-group), Neochrysis lecointei (Ducke), Pleurochrysis ancilla (Buysson) and P. lynchi (Bréthes). This paper reports new data about host–parasite relationships and life cycles for these species. Multiple parasites (from one species or from different families of insects) emerged from single cells of some parasitised nests: from each host cell parasitised by species of Pleurochrysis, two adults emerged successfully, information previously unknown for the genus; and in three cases of cells parasitised by C. boutheryi, two adults successfully emerged from a single cell; in two cases both individuals were chrysidine, and in third one was chrysidine and one Leucospis pulchripes (Leucospidae).